2013
DOI: 10.1371/journal.pone.0072603
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Hyperoxia Accelerates Fracture Healing in Mice

Abstract: Increased oxygen tension influences bone metabolism. This study comprised two main experiments: one aimed to determine the bone mineral apposition and bone formation rates in vivo under hyperbaric hyperoxia (HBO), and the other aimed to evaluate the effects of exposure to HBO on fracture healing. In experiment 1, male mice were exposed to HBO [90 min/day at 90% O2 at 2 atmospheres absolute (ATA) for 5 days]. In experiment 2, an open femur fracture model was created in mice, followed by exposure to HBO 5 times/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
12

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 23 publications
5
29
0
12
Order By: Relevance
“…Preservation of fracture haematoma, respectful surgery to soft tissueespecially periosteum around fracture site, proper fixation and surgical approach choice, fighting against infections peroperatively, micromovement of fracture site after stabilization contributes healing. Hyperbaric oxygen therapy for selected patients may contribute and experimental researches exist in the literature (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of fracture haematoma, respectful surgery to soft tissueespecially periosteum around fracture site, proper fixation and surgical approach choice, fighting against infections peroperatively, micromovement of fracture site after stabilization contributes healing. Hyperbaric oxygen therapy for selected patients may contribute and experimental researches exist in the literature (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Although HBO is an established modality in the treatment of many disorders and has been successfully used in clinical conditions related to ischemia and/or hypoxia [4,5,6], HBO therapy is still under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…HBO therapy has already been successfully used to improve bone healing [4,5,6] because it also stimulates angiogenesis and osteogenesis [4,7]. The molecular mechanisms of HBO on bone formation may be mediated via increased osteogenic differentiation, which is related to Runx2 production [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing effect of HBO on the bone formation and repair can be demonstrated as another action of mechanism. It has been revealed that HBO, which speeds up fracture healing, increases type 1 collagen formation from osteoblasts and alkaline phosphatase activity (11).…”
Section: Discussionmentioning
confidence: 99%